DEVELOPMENT STRATEGY OF POTENTIAL VILLAGE TO BE VILLAGE OF EDUCATION TOURISM IN BUMI JAYA VILLAGE (Case Study of Bumi Jaya Pottery Craft Center in Ciruas District, Serang Regency) - Arta Rusidarma Putra; S. Silfiana (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2019)
ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui strategi pengembangan potensi desa wisata edukasi Bumi Jaya yang terkenal dengan kerajinan gerabah dan keindahan alamnya. Kerajinan gerabah yang ada di Desa Bumi Jaya Kecamatan Ciruas Kabupaten Serang merupakan salah satu desa yang sangat berpotensi untuk pengembangan menjadi desa wisata edukasi. Selain dijadikan sebagai sentra kerajinan gerabah, desa ini memiliki sumber daya alam yang sangat mendukung terutama pada tersedianya bahan baku tanah liat yang mempunyai kualitas yang sangat baik dan juga sejarah kearifan lokal gerabah dari jaman kerajaan Banten serta keindahan alam persawahannya. Untuk lebih meningkatkan perekonomian masyarakat, maka dirasa perlu adanya pengembangan potensi desa menjadi desa wisata edukasi Bumi Jaya. Strategi pengembangan potensi desa wisata edukasi Bumi Jaya dengan perencanaan partisipatif dalam pengembangan pariwisata di desa wisata Bumi Jaya dan menerapkan Community Based Tourism sebagai pendekatan pengembangan pariwisata. Penelitian ini menggunakan metode deskriptif kualitatif. Berdasarkan hasil penelitian, pengembangan strategi wisata edukasi Bumi Jaya dapat dirumuskan dengan menggunakan SWOT dan strategi analisis SO, ST, WO, WT. Kata Kunci : Strategi Pengembangan, Potensi, Desa Wisata Edukasi ABSTRACTThe purpose of this study was to determine the potential development strategies of Bumi Jaya educational tourism villages that are famous for pottery crafts and their natural beauty. Pottery crafts in Bumi Jaya Village, Ciruas Subdistrict, Serang Regency are one of the villages that have the potential to develop into educational tourism villages. In addition to being used as a center for earthenware crafts, this village has natural resources that are very supportive especially in the availability of clay raw materials that have very good quality and also the history of the local wisdom of pottery from Banten's royal era and the natural beauty of its rice fields. To further improve the economy of the community, it is deemed necessary to develop the potential of the village to become an educational tourism village for Bumi Jaya. The strategy for developing the potential of educational tourism villages in Bumi Jaya with participatory planning in tourism development in the tourism village of Bumi Jaya and implementing Community Based Tourism as an approach to tourism development. This study used descriptive qualitative method. Based on the results of the research, the development of the Bumi Jaya educational tourism strategy can be formulated using SWOT and SO, ST, WO, WT analysis strategies. Keywords: Development Strategy, Potential, Educational Tourism Village.